The greatest my own story - Ali, Muhammad (Graymalkin Media, 2015)
In his own words, the heavyweight champion of the world pulls no punches as he chronicles the battles he faced in and out of the ring in this fascinating memoir edited by Nobel Prize-winning novelist, Toni Morrison.
Keywords: Ali, Muhammad, 1942-2016.